1968
DOI: 10.2307/1948535
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Effects of Short Term Ionizing Radiation on Old‐Field Succession

Abstract: TABLE 4. Life history stages of flood plain successional species. R= rosette or germinant stage, S= stem elongation, F= flower or fruit, D= dormant or seed only, r= occurs in irradiated field, c= occurs in control field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1969
1969
1986
1986

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Streu and Vasvary ( 1967) have shown that high soil moisture levels can offset the effects of soil treatments with organophosphate insecticides, including diazinon, on vegetation growth in turf grass communities. Vegetation differences induced by other stresses such as ionizing radiation have also been offset by increased soil moisture levels (Daniel and Platt 1968) . Several mechanisms have been proposed to explain the vegetative enrichment following soil contamination with organophosphate insecticides in agricultural (Tarjan 1964, Winchester and Burt 1964, Streu and Vasvary 1966 and old-field (Malone 1969) communities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Streu and Vasvary ( 1967) have shown that high soil moisture levels can offset the effects of soil treatments with organophosphate insecticides, including diazinon, on vegetation growth in turf grass communities. Vegetation differences induced by other stresses such as ionizing radiation have also been offset by increased soil moisture levels (Daniel and Platt 1968) . Several mechanisms have been proposed to explain the vegetative enrichment following soil contamination with organophosphate insecticides in agricultural (Tarjan 1964, Winchester and Burt 1964, Streu and Vasvary 1966 and old-field (Malone 1969) communities.…”
Section: Discussionmentioning
confidence: 99%
“…Moore (1967) found that plant diversification occurred when a pesticide caused the removal of a dominant overstory species in a forest community. Several studies concerning the effects of ionizing radiation on old-field vegetation (McCormick and Platt 1962, Woodwell and Oosting 1965, Daniel and Platt 1968 have indicated an increased abundance of radioresistant species by release from competition with radiosensitive species.…”
Section: Discussionmentioning
confidence: 99%
“…Many recent studies have been concerned with the structural (dominance; diversity) and functional (biomass; productivity) responses of communities to various perturbations, including species removal (Allen and Forman 1976, Sutherland 1977, Vance 1979, toxic chemicals (Barrett 1968, Malone 1969, Shure 1971, Pomeroy and Barrett 1975, Tomkins and Grant 1977, Wakefield and Barrett 1979, nutrient enrichment (Harcombe 1977, Kirchner 1977, Bakelaar and Odum 1978, fire (Hulbert 1969, Lloyd 1972, Lussenhop 1976, and ionizing radiation (McCormick and Platt 1962, Daniel and Platt 1968, Armentano and Woodwell 1976. These studies demonstrate that an external perturbation can lead to complex changes in the structure and function of communities.…”
Section: Introductionmentioning
confidence: 99%
“…Community studies have traditionally been descriptive (Golley 1965, Whittaker 1965, McNaughton 1968, Vogl 1969. A few experimental studies have attempted to deal with the relationship between diversity and stability in community ecosystems (Hairston et al 1968, Flaherty 1969, and some researchers have examined the influence of various types of stress on the structure and function of communities (Crossley and Howden 1961, Malone et al 1967, Barrett 1968, Daniel and Platt 1968, Malone 1969, Anderson 1970, Dunn 1970, Ewing and Dorris 1970, Bulan and Barrett 1971, Hall et al 1971, Hanes 1971, Shure 1971. Rosensweig (1971) has discussed theoretically some problems involved with ecosystem enrichment.…”
Section: Introductionmentioning
confidence: 99%